FAMILY ENVIRONMENT AND ENTREPRENEURIAL MOTIVATION AS PREDICTORS OF ENTREPRENEURIAL INTEREST AMONG VOCATIONAL STUDENTS IN EAST JAKARTA - Sirait, Marthina Selsa; Nurmalasari, Dewi; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to determine the influence of family environment and entrepreneurial motivation on entrepreneurial interest of vocational high school students in East Jakarta. The method used is a quantitative survey with proportionate stratified random sampling technique based on the Isaac and Michael formula, resulting in a sample of 138 students from a total of 216 students of grades X and XI majoring in Office Management and Business Services at SMKN 40, 48, and 50 Jakarta. Data analysis was carried out using SEM (Structural Equation Modeling) with the help of SmartPLS 4.0 software. The test results show that Family Environment and Entrepreneurial Motivation have a positive and significant effect on Entrepreneurial Interest. The path coefficient values are 0.495 and 0.518, respectively, with t-statistic > 1.96 and p-value 0.000. Simultaneously, both variables explain 69.4% of the variation in Entrepreneurial Interest (R-square = 0.694).